Analisis Profil Literasi Sains Calon Guru Fisika pada Materi Optika Geometri - Putra, Awallukyta Krisnata; Rusilowati, Ani (UPEJ Unnes Physics Education Journal, 2021)
This research aims to determine the profile of scientific literacy aspects of knowledge, aspects of competence / process, aspects of attitude to science, and factors that influence scientific literacy of pre-service students of Physics teachers. The subjects of this study were pre-service students of Physics teachers in Universitas Negeri Semarang. The instrument was in the form of a scientific literacy-based evaluation tool with 25 items in multiple choice geometric optics and a science attitude questionnaire. Quantitative data analysis techniques using parametric statistics and qualitative data analysis using triangulation technique. The results showed that the percentage of science literacy scores in the knowledge aspect was categorized as Ã¢â‚¬Å“very lessÃ¢â‚¬Â by 37.76%, the percentage of science literacy scores in the competency / process aspect was categorized as Ã¢â‚¬Å“sufficientÃ¢â‚¬Â by 63,58%, the percentage of scientific literacy scores in the attitude aspect of science was Ã¢â‚¬Å“sufficientÃ¢â‚¬Â by 74,78%. Factors that influence scientific literacy of pre-service Physics teacher students include the interest of physics teacher students in science and experience working on scientific literacy-based evaluation instruments. Based on the results of the study, it can be concluded that the scientific literacy profile of students of UNNES Physics teacher candidates is categorized as very less on the knowledge aspect and classified as sufficient category on the aspects of skills / processes and aspects of scientific attitudes.